Acrylamide determination during an industrial roasting process of coffee and the influence of asparagine and low molecular weight sugars. (15th January 2020) - Bertuzzi, Terenzio; Martinelli, Erika; Mulazzi, Annalisa; Rastelli, Silvia
Highlights: Acrylamide determination during an industrial roasting process of coffee was carried out. The temperature of roasting increased from 90° to about 215 °C. Acrylamide content reached the maximum value at 175–177 °C, then quickly decreased. Fructose and glucose levels increased about 5 and 10-times, while sucrose decreased. Abstract: The formation and partial degradation of acrylamide (AA), asparagine and low molecular weight sugars were evaluated during an industrial coffee roasting process, in which the temperature increased from 90° to about 215 °C. Arabica and Robusta varieties were roasted individually. AA content reached the maximum value at 10 min, corresponding to a temperature of 175–177 °C (1045 ± 28 and 795 ± 25 µg kg −1 for Arabica and Robusta, respectively). Successively, AA content decreased very quickly and at 14 min (203–205 °C) its concentration was lower than the benchmark level of 400 µg kg −1 for roast coffee set by the EU Commission Regulation (2017/2158). In the final product, AA content was close to 300 µg kg −1 . Asparagine quickly decreased; contrary, the concentration of fructose and glucose increased reaching their maximum value at 12 min. Then, a quick degradation occurred; their increase could be mainly due to the hydrolysis of sucrose, which decreased in the same period.